Marginal adaptation of a sintered ceramic inlay system before and after cementation - (:unkn) unknown (BLACKWELL SCIENCE LTD, 1997)
The long term clinical performance of porcelain inlays depends on a number of factors and the marginal adaptation is one of significant interest. The purpose of this in vitro study was to evaluate the marginal integrity of a sintered inlay technique (Ducera(R)), before and after cementation. MOD cavities without bevels were prepared on 10 human mandibular molar teeth and porcelain inlays were fabricated according to the manufacturer's instructions. Mays were evaluated microscopically for their adaptation to the occlusal and approximal margins of the tooth by means of a replica technique. Inlays were cemented with a dual-cured hybrid composite luting material (Enforce(R)). After polishing, each tooth was sectioned in buccal/lingual and mesial/distal directions following the same procedure in the sectioning of replicas. The marginal gap and the thickness of exposed cement were measured at each section. The mean marginal gap of 71.83 +/- 8.93 mu m recorded for the occlusal margin before cementation was significantly smaller than that of 105.6 +/- 39.33 mu m calculated at the approximal margin. Following the cementation, the adaptation of the inlays at the occlusal margin was also found to be superior to that of the approximal margin. Comparison of mean gap values before and after cementation revealed that the marginal gap increased by 6.94 mu m and 23.25 mu m at the occlusal and approximal margins, respectively. Although polishing was performed after cementation, excess luting material was still observed, that caused an increase in the width of the exposed luting cement.
Keywords: IN-VITRO; COMPOSITE; FIT